Patient’s Cancer Categorization Based On Jaccard and Venn Techniques - Nurul Aswa Omar; Riswan Efendi; Norfaradilla Wahid; Afiq Luqman Mohd Yasin (JOIV : International Journal on Informatics Visualization, 2018)
Under some circumstances, hospitals and clinics need to know the preliminary patient’s disease categorization, such as H1N1, Dengue, HIV/AIDS and others. However, categorizing patients will be useful in the future if the hospitals  properly recorded their patient criteria and crucial details such as patient’s name, symptoms, temperature and others. There are many benefits by grouping the patients together such as the hospitals will know how to provide an appropriate medicine to the patient, which patient will get the highest priority and should be quarantined.  It is very important to know how to group the patients by using their symptoms detected. This study will focus on patients with cancer problems using Jaccard index and Venn diagram techniques. Their data will be collected from a hospital and the patients are selected randomly. Patients with lungs, brain and breast cancer will be selected in this study.